Femoral Stress Changes after Total Hip Arthroplasty with the Ribbed Prosthesis: A Finite Element Analysis. (23rd March 2020) - Luo, Changqi; Wu, Xiang-Dong; Wan, Yifei; Liao, Junyi; Cheng, Qiang; Tian, Mian; Bai, Zhibiao; Huang, Wei
Abstract : Background . A total hip reconstruction is related to the stress distribution throughout the prosthesis, cement, and femur. Researches on reducing the stress in all components to minimize the risk of failure are of great significance. The objective of our study was to determine the biomechanical variation in overall femoral stress and periprosthetic femoral stress distribution after implantation with the Ribbed anatomic prosthesis. Methods . Three-dimensional finite element models of intact femur and Ribbed prosthesis were developed according to the morphology, while the hip joint loading and the strength of related muscles were applied in the models. The overall stress changes of the intact femur before and after the implantation were analyzed, and the periprosthetic stress distribution especially in the proximal region of the femur was quantified. Results . As a result, the overall stress pattern of the femur did not change after the implantation compared with the intact femur. The region of peak stress value was located in the middle and lower segments of the full length femur, but the stress value level decreased. The final prosthesis resulted in a significant decrease in the equivalent stress level of the periprosthetic bone tissue, and the most severe area appeared at the endmost posterior quadrant. The stress shielding ratio of the Ribbed prosthesis was 71.6%. The stress value level gradually increased towards the distal part of the prosthesis and recovered to physiological level at the end of the prosthesis. Conclusions . The Ribbed prosthesis can cause significant stress shielding effect in the proximal femur. These results may help optimize prosthetic design to reduce stress shielding effect and improve clinical outcomes.